2022
DOI: 10.3390/pathogens11101113
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Cancer Presenting with Absceding Infection Due to Fusobacterium nucleatum

Abstract: Intestinal microbiota such as Fusobacterium nucleatum play an important role in the pathogenesis of colorectal cancer. Here, we describe the case of a 47-year-old patient presenting with endophthalmitis and a liver abscess due to Fusobacterium nucleatum that prompted the diagnosis of colorectal cancer as the most likely source of infection. This case highlights that colorectal cancer needs to be considered in patients with systemic infection with Fusobacterium nucleatum and colonoscopy should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Many reports have confirmed that Fn exists near and in CRC cells (Su et al, 1992), Fn adheres to the cell surface (Engevik et al, 2021), this bacterium can reduce the body's immune regulation (Zundler et al, 2022), and stimulate the proliferation and metastasis of cancer cells (Kostic et al, 2013). Fn was added to the culture medium of CRC and observed by light microscopy as in Figure 1a, compared to the control group (A), the HT29 and HCT116 cells grew faster which co-culture with Fn, and had more cells in the same area, along with a more pronounced darker shade around the cells.…”
Section: Observation Of Co-culture Of Crc Cells With Fusobacterium Nu...mentioning
confidence: 94%
“…Many reports have confirmed that Fn exists near and in CRC cells (Su et al, 1992), Fn adheres to the cell surface (Engevik et al, 2021), this bacterium can reduce the body's immune regulation (Zundler et al, 2022), and stimulate the proliferation and metastasis of cancer cells (Kostic et al, 2013). Fn was added to the culture medium of CRC and observed by light microscopy as in Figure 1a, compared to the control group (A), the HT29 and HCT116 cells grew faster which co-culture with Fn, and had more cells in the same area, along with a more pronounced darker shade around the cells.…”
Section: Observation Of Co-culture Of Crc Cells With Fusobacterium Nu...mentioning
confidence: 94%
“…The progression from precancerous adenomatous polyps to adenocarcinoma generally takes about 10 years [ 5 ], and is considered to be the consequence of host mutations that accumulate over time. Improved methods for detecting microorganisms and new insights into the human microbiome have led to a new perspective on several diseases, including CRC [ 6 , 7 , 8 ]. According to recent research, this cancer is linked with altered gut microbiota [ 9 ] and aided by the anaerobic gram-negative bacteria F. nucleatum [ 4 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is often linked to advanced disease, chemoresistance, distant metastases, and a poor prognosis [ 13 , 14 , 15 ]. Additional studies have demonstrated that F. nucleatum promotes carcinogenesis, changes lymphocyte infiltration of tumor-infiltrating lymphocytes, suppresses NK cell and tumor-infiltrating T cell death, and enhances resistance to chemotherapy in colon cancer [ 7 , 15 , 16 ]. Fusobacteria linked to CRC develops in the oral microbiome and reaches the colon through hematogenous rather than gastrointestinal routes.…”
Section: Introductionmentioning
confidence: 99%